Philanthropic Fundraising of Higher Education Institutions: A Review of the Malaysian and Australian Perspectives - Mohd Isa, Rohayati; Youhanna, Najdi; John C., Williamson (MDPI AG, 2016)
Currently, higher education institutions are facing rapidly rising costs and limitations in governmental funding. Accordingly, higher education institutions need sustainable forms of funding to operate effectively and remain competitive. In their attempts to identify causes and initiatives, world universities have paid more attention to philanthropic support. In their effort to raise funds, many institutions have grappled with questions of why donors give and what motivates donors to give. To address these questions, scholars must consider the influence of demographic and socio-economic characteristics, as well as internal and external motivational parameters on successful giving behaviour. However, much more attention has been paid to universities in Western countries and the United States. This study aims to review the factors influencing organizational philanthropic fundraising success and to gain an understanding of factors affecting donors’ giving decisions and perceptions of giving. This work focuses on donors’ giving to Malaysian and Australian public universities.